Wittgenstein and justice - Pitkin, Hanna (Berkeley University of California Press, 1972)
Hanna Pitkin argues that Wittgenstein's later philosophy offers a revolutionary new conception of language, and hence a new and deeper understanding of ourselves and the world of human institutions and action. Hanna Pitkin argues that Wittgenstein's later philosophy offers a revolutionary new conception of language, and hence a new and deeper understanding of ourselves and the world of human institutions and action.